Minerals - Essa, Khalid S. (IntechOpen, 2019)
The book "Minerals" offers an important and thorough overview on different geophysical methods including gravity, magnetic and self-potential in mineral exploration, as well as physical and chemical analysis in delineating the minerals. Furthermore, the book describes the different types of minerals such as clay and its minerals, and uranium (which contains radioactive elements) and how to use them in the sector of safe energy. The book also demonstrates the governing law of mineral distribution in bearing rocks and their journey from mining to marketing. This book shall be of great interest to students, geologists, geophysicists, and the mining investment community.